KUALITAS MINYAK GORENG CURAH YANG BERADA DI PASAR TRADISIONAL DI DAERAH JABOTABEK PADA BERBAGAI PENYIMPANAN - Eva Yulia; ade Heri Mulyati; Farida Nuraeni (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2017)
Handling of bulk cooking oil is not good, cause a decrease in the quality of cooking oil when in storage in the selling process. Wrapping packaging of bulk cooking oil that is not appropriate and direct interaction with the sun and microbes can change the quality of cooking oil. Besides the fabrication of bulk cooking oil, to make people uneasy. For it is necessary for the analysis of bulk cooking oil quality on a variety of storage (closed and open) in the traditional markets in in Jabotabek Area through the physical trials and chemical tests. Analysis physics for odor and color is done organoleptic. Chemical analysis of water content using gravimetric method. Determined acid number by titration of alkalimetri with NaOH. Peroxide number determined with Tio 0.02 N. For example pelicans oil test alcohol 5N KOH.Based on this research, to test the physics of odor obtained normal results for sealed storage and smelling a bit stale at week 4 and to 5 in the open storage, while the average for the color of pale yellow oil, yellow, until golden brown. To test the chemical in terms of water content and acid number in the average closed storage meets the requirements of ISO - 3741 - 2002, while the open storage of the average moisture content does not meet the requirements for the number of acid still meet the quality standards II. The results of the analysis of peroxide numbers in a closed storage on average to meet the requirements of ISO - 3741 - 1995, while the open storage do not meet the standards. To test the oil did not reveal any falsification pelicans.Â Keywords : analysis, cooking oil, gravimetry, alkalimetry titration